Reading disorders and dyslexia. - Hulme, C; Snowling, M (Lippincott, Williams & Wilkins, 2016)
We review current knowledge about the nature of reading development and disorders, distinguishing between the processes involved in learning to decode print, and the processes involved in reading comprehension. Difficulties in learning to read appear to be predominantly caused by deficits in underlying oral language skills and children with decoding difficulties/dyslexia experience deficits in phoneme awareness, letter-sound knowledge and rapid automatized naming in the preschool years and beyond. We report data from a prospective study of children at high risk of dyslexia to show that being at family-risk of dyslexia is a primary risk factor for poor reading and children with persistent language difficulties at school entry are more likely to be diagnosed. Implications for screening and for the delivery of robust interventions for language and reading are discussed.